Intracavernous Carotid Artery Aneurysm in a Case of Tolosa-Hunt Syndrome - Turkcuoglu, Peykan; Kaan Kaya, Mehmet; Yildirim, Hanefi; Deniz, Nurettin; Celiker, Ulku (Annals of Medical Research, 2021)
None
Keywords: Intracavernous carotid artery aneurysm, Tolosa-Hunt Syndrome, Neuroimaging